1995
DOI: 10.1002/jez.1402730104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of space flight on Xenopus laevis larval development

Abstract: Fifty-three fertilized Xenopus laevis embryos at early tail bud stage were launched into orbit aboard a Biocosmos satellite and remained in microgravity for 11.5 days. During this period, the embryos hatched and continued to develop as free-living larvae. Forty-eight individuals survived the mission. Upon recovery these tadpoles had smaller heads/bodies and proportionately longer tails than ground controls. Almost all the flight animals had caudal lordosis and consequently swam in backward somersaults. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 16 publications
2
29
1
Order By: Relevance
“…Although NCC derived elements make up more of the head skeleton and are thus more readily observed than mesodermal elements, we found that the only mesodermal element measured, the notochord, did not vary significantly among groups. We did not observe many of the spaceflight microgravity effects noted by Snetkova et al (1995), such as significant differences in body or tail length, caudal lordosis, or changes in notochord size and shape. But we did observe similar effects on the branchial basket, notably a more spherical shape and possibly less development of the gill filters.…”
Section: Cell Proliferation In Four Tissues Of Embryos Developing In contrasting
confidence: 73%
See 2 more Smart Citations
“…Although NCC derived elements make up more of the head skeleton and are thus more readily observed than mesodermal elements, we found that the only mesodermal element measured, the notochord, did not vary significantly among groups. We did not observe many of the spaceflight microgravity effects noted by Snetkova et al (1995), such as significant differences in body or tail length, caudal lordosis, or changes in notochord size and shape. But we did observe similar effects on the branchial basket, notably a more spherical shape and possibly less development of the gill filters.…”
Section: Cell Proliferation In Four Tissues Of Embryos Developing In contrasting
confidence: 73%
“…The tadpoles, launched at the early tailbud stage (approximately one day old), exhibited caudal lordosis (also noted in a study by Horn, 2006), disproportionately long tails and short bodies, a failure to inflate their lungs, and a reduced, misshapen branchial apparatus (Snetkova et al, 1995). The acceleration and vibration of the launch and the sudden onset of μG may have caused or contributed to these irregularities.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Behavioral modifications included swimming abnormalities Snetkova et al, 1995;Fejtek et al, 1998) and a depression of both gain and amplitude of the roll-induced static vestibuloocular reflex (rVOR) but not of the dynamic VOR induced by horizontal lateral displacements (Eßeling et al, 1994a;Eßeling et al, 1994b). Morphological modifications include a hyperextension of the tail (tail lordosis) (Fig.·1), and were observed in Xenopus laevis tadpoles launched before hatching (Snetkova et al, 1995;Sebastian and Horn, 1998) but not in tadpoles that developed from eggs fertilized in orbit under microgravity (Souza et al, 1995) (cf. Table·1).…”
Section: Introductionmentioning
confidence: 99%
“…Tail lordosis might be caused by weight deloading during g-exposure because affected tadpoles showed muscle degeneration (Snetkova et al, 1995). However, other factors such as: (1) trophic effects of vestibular activity on muscle development, and (2) the rostrocaudal maturation gradient, might cause tail lordosis if they revealed a sensitivity to altered gravity.…”
Section: Introductionmentioning
confidence: 99%